Dynamics of the seasonally dry tropical forests of the Marañón Valley, northern Peru - José Luis Marcelo-Peña; Karim Rocío López-Fernandez; Carlos Reynel R․; Reynaldo Linares-Palomino; Kyle Dexter (Trees, Forests and People, 2025)
The seasonally dry tropical forest (SDTF) is one of the most threatened biomes in the world. In northern Peru, the dry ecosystems of the Marañón Valley are particularly significant at a tropical level due to their remarkably high levels of endemism, yet they face serious threats. We assessed changes over time in species richness, diversity, composition, and structure of the SDTF, analyzing how the dynamics of this biome manifest at both local and regional scales. To achieve this, we conducted re-measurements of permanent plots of 0.5 ha. Our results indicate that in the region, changes in species richness, diversity, and floristic composition remain stable. We found that both recruitment (0.4 - 4.7 %) and mortality rates (1.1 - 4.3 %) vary widely among plots, but are higher on average than lowland tropical rainforests, indicative of greater dynamism. We found that recruitment rates are more than double the mortality rates. Furthermore, eighteen species showed no recruitment during our study period, while ten species that did recruit experienced mortality rates exceeding recruitment by 100 %. The structure of the SDTF in the Marañón Valley is not in equilibrium and is changing over time. Continued long-term studies using standardized methodologies are essential to understand the critical ecological processes in these SDTFs.